A RARE SKELETAL DYSPLASIA-CLOSE MIMICKER OF JUVENILE IDIOPATHIC ARTHRITIS-PROGRESSIVE PSEUDORHEUMATOID DYSPLASIA - Riaz , Maira; Khoso, Zubair; Rai, Versha Rani; Hanif, Misbah Iqbal; Ibrahim, Mohsina Noor; Raza, Syed Jamal (Journal of Ayub Medical College Abbottabad, 2022)
Progressive pseudorheumatoid dysplasia or spondyloepiphyseal dysplasia tarda is caused by a mutation in Wnt1 inducible signalling pathway protein 3 (WISP3) and passes in an autosomal recessive manner. Prevalence underestimated as one per million and most of the cases remain undiagnosed or treated as Juvenile Idiopathic Arthritis (JIA). Differentiation between JIA and PPRD is really challenging however, this case is genetically confirmed from our country. 7-year-old, short stature boy, with multiple joint swellings of hands and feet, initially suspected to have JIA and had been worked up and took treatment for that for the past 2 years. He had progressive stiffness of small joints. Baseline biochemistry, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor and ANA, were within normal limits. He was moderately growth hormone deficient. Thyroid function tests and insulin-like growth factor 1 (IGF-1) were within reference ranges. Skeletal survey showed typical findings of pseudorheumatoid skeletal dysplasia. Physical therapy and genetic counselling were done.